COVID-19 Pandemic and the Burden of Internet Addiction in the United States - Jagdish Khubchandani; Sushil Sharma; James H. Price (Psychiatry International, 2021)
Despite the extensive usage of the internet, little is known about internet addiction among Americans during the pandemic. A valid and reliable questionnaire was deployed online via MTurk to recruit a national sample of adult Americans to understand the nature and extent of internet addiction. A total of 1305 individuals participated in the study where the majority were males (64%), whites (78%), non-Hispanic (70%), married (72%), 18–35 years old (57%), employed full time (86%), and with a Bachelor’s degree or higher (83%). The prevalence of internet addiction was distributed as no addiction (45%), probable addiction or risk of addiction (41%), and definite or severe addiction (14%). More than a fourth of the population had depression (28%) or anxiety (25%). Despite adjusting for sociodemographic characteristics, definite/severe internet addiction was strongly predictive of depression, anxiety, and psychological distress in multiple regression analyses. Those who were probably addicted or at risk of addiction were also more likely to have depression or anxiety. Compared to estimates before the pandemic, this study suggests an increase in internet addiction among U.S. adults during the COVID-19 pandemic. Population-based interventions and mental health promotion strategies should focus on a reduction in internet consumption and screen time.